Synthesis and biological evaluation of novel pyrazoline derivatives as potent anti-inflammatory agents. Issue 11 (1st June 2015) - He, Jiqiang; Ma, Liang; Wei, Zhe; Zhu, Jun; Peng, Fei; Shao, Mingfeng; Lei, Lei; He, Lin; Tang, Minghai; He, Linhong; Wu, Yuzhe; Chen, Lijuan
Graphical abstract: Abstract: Twenty-eight pyrazoline derivatives, which originated from pyranochalcones, have been synthesized and evaluated for their inhibitory potency on the production of inflammatory mediator nitric oxide (NO) in LPS-stimulated RAW 264.7 cells. Among them, three compounds (1c, 11c, and15c ) exhibited potent inhibitory effects on NO production and iNOS activity superior to positive control Indomethacin, with1c being most efficacious. Furthermore, 1c could suppress the progress of carrageenan-induced hind paw edema at a dosage of 50 mg/kg/day and dose-dependently ameliorate the development of adjuvant-induced arthritis (AIA). Docking study confirmed that1c was an iNOS inhibitor with good binding into the active site of murine iNOS.